Fatty acid composition in the macroalgae Gracilaria caudata , G. birdiae and G. domingensis obtained at Icapuí county, Ceará State - Di Souza, Luiz; Pinto, Carlos Henrique Catunda; Matias, Luiz Gonzaga de Oliveira; Santos, Anne Gabriella Dias; Rebouças, Rosinere Ferreira da Costa; Gomes, Anderson Fernandes (Arquivos de Ciências do Mar, 2015)
This paper puts forth the composition of fatty acids present in the red seaweeds Gracilaria caudata, Gracilaria birdiae and Gracilaria domingensis , which are meant as an outstanding source of raw materials used in the preparation of biofuels. The analyzed material was collected at Icapuí county, Ceará State, Northeast Brazil, with the macroalgae being submitted to washing and, afterwards, carried in a thermal container over to the laboratory of Chemistry, University of Rio Grande do Norte at Mossoró, where they were dried in an oven for 24 hours, and then ground in an industrial shredder. Lipids were extracted with a Soxleht device using hexane as a solvent and then subjected to a hydro-esterification reaction coming first a basic hydrolysis and later on the reaction itself with the fatty acids using iodine as a catalyst to yield the methyl and ethyl esters. The products were analyzed into a GC/MS and the results were compared with the literature data on genus Gracilaria from other Brazilian regions.